Computer Simulation of Replaceable Many Sider Plates (RMSP) with Enhanced Chip-Breaking Characteristics; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Korchuganova M. A. Marina Anatolievna; Syrbakov A. P. Andrey Pavlovich; Chernysheva T. Yu. Tatiana Yurievna; Ivanov G.; Gnedasch E. (2016, 2016)
Title screen